Restructuring of Electronic Waste Management in Batam City by Strengthening Legal System - Priyono, FX.Joko; Hartono, Darminto; Farida, Elfia; Wekke, Ismail Suardi (International Journal of Engineering and Technology, 2018)
The problem of managing electronic waste in the city of Batam is so complex because the prevailing laws and regulations do not work properly. Even electronic waste is clearly traded both legal and illegal. No firm action from law enforcers while stakeholders do not care. The condition reflects the legal system is not working and needs reconstruction. Through focus group discussions (FGDs) involving key informants can be expressed in terms of substance, structure, and legal culture. The main problem of the three elements of the legal system is the rule-sanctioning institutions which is reflected by the weakness of the interpretation of the rule of law, the mentality of the apparatus, and the quality of the judge's decision in deciding the case of hazardous and toxic waste materials which have less deterrent effect for the perpetrators of electronic waste importers and circulation. This condition is exacerbated by the legal culture of the society that is less conducive to the handling of electronic waste. To reconstruct the condition, it is necessary to strengthen the legal system through the establishment of local regulations that specifically regulate electronic waste, rule-making institution empowerment, a revolution of bureaucrats and law enforcers mentality, community empowerment of electronic waste hazards, and training of safely electronic waste processing.